Service Quality and Customer Satisfaction in Public Transports - Filipa Fonseca (2010)
The objective of the paper is to identify the determinants of servicequality as well as its impact on the satisfaction of public transport commuters.The paper explores the relationship between service quality and customersatisfaction in a public transport service taking into account both internal andexternal perspectives. In order to analyse this relationship, the concepts ofservice quality, consumer satisfaction and dissatisfaction are assessed. Amodel of analysis is developed aiming at explaining this relationship andguiding the empirical study. This is based on an exploratory case study of ametro company in Europe. The results of the study put in evidence two keyfindings. The first is related to the level of service quality in its maindimensions. We conclude that reliability, security, speed, comfort andpunctuality are quality dimensions of greater importance for the publictransport services. Secondly, the study explores satisfaction and theirdeterminants. Despite literature stipulates the existence of a distinctionbetween the constructs of quality and satisfaction, this study found that thetransport company, non-customers and customers clearly do not make such adistinction.